Volare: poems by Sônia Cintra (Per Musi, 2021)
The song cycle Volare, for low-pitched female voice and string orchestra, was created from Sônia Cintra (1949-2018) poems readings. Altogether, the cycle consists of 11 songs and 2 interludes that can be played in a full or reduced version. The instrumentation of the cycle is variable. There are songs that use the string orchestra in its entirety and there are songs that partially use the available instruments. Volare was composed in 2018 and premiered in 2019 during the 23rd Biennial of Contemporary Brazilian Music.